Optimization of Chain Pillars Design in Longwall Mining Method - Navid Hosseini; Kazem Oraee; Mehran Gholincjad (International Conference on Ground Control in Mining, 2010)
"Chain coal pillars are pans of the structure of longwall mining system that play a significant role in the stability of the entries. With mechanization and developments in the various aspects of the method, higher efficiency in optimization of the design of chain coal pillars seems appropriate. In this paper the three main methods of chain pillar design, namely the empirical analytical and numerical methods arc compared. Real data from the Tabaslran coal mines have been used in order to make the comparison process reliable. It is concluded that the most apparent advantage of the empirical method is the reliability of the results while the use of numerical methods enjoys the advantage of flexibility. On the other hand the analytical methods are complex unless simplifying assumptions arc made that can substantially decrease the accuracy of result which is thought to be the main advantage of the design method. A new method is therefore introduced here that combines all of the three presently used methods and by doing so the new method has the advantages of the three while minimizing complexities and inaccuracies associated with the use of the individual methods.INTRODUCTIONLongwall mining is a high production method that can use mechanization to its full extent. Its initial development can be traced to 17th century European collieries but it was not until the second half of the 20th century with the development of self advancing support systems that the method gained popularity in the USA (Oraec. 2001). During the last decade, the production of longwall faces has increased significantly (Peng. 2006). The ability for mechanization along with good safety condition is the main reasons for such development. In the longwall mining method a good design for panel and entries on both sides, are two essential parameters. In this method, the thickness of overburden (depth of mine) nom1ally ranges from 60 to 20 m (197 to 2.7 9 ft) (Hartman, 2000) and with increasing mine depth designing for stabilizing the entries on both sides of the panel become more difficult. Thus, for safety and stability the size of chain pillar must increase. This causes the overall coal recovery to decrease and increase mining costs per ton. As such wide pillars hinder the air flow and hence ventilation costs increases too. Therefore with accurate identification of loading conditions and stress analysis. pillar that are a minimum size and sufficient safety factor are carefully designed."